Effect of steaming and gibberellic acid on growth, yield and nutritional quality of Calocybe indica - SOHLIYA, D.S.R.; GOGOI, ROBIN; PUZARI, K.C.; SARMAH, D.K.; CHELLENG, ANURADHA (Indian Phytopathology, 2011)
An experiment was carried out on the effect of period of steaming for pasteurization of straw and gibberellic acid on the growth of milky mushroom (Calocybe indica). Direct steaming of straw for 1 hr and also for 30 min was practiced with application of gibberellic acid (GA3) at three different concentrations before spawning was done. It revealed that steaming and GA3 application increased the duration of mycelial run with reduction in yield of milky mushroom but it increased the protein content of fruit bodies as compared to control. The yield in the normal practice of boiling of straw for 1hr and sun drying was found better than steaming.